2014
DOI: 10.1021/nl500859p
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Cellulose under Ammonia Leads to Nitrogen-Doped Nanoporous Carbon Generated through Methane Formation

Abstract: Here, we present a simple one-step fabrication methodology for nitrogen-doped (N-doped) nanoporous carbon membranes via annealing cellulose filter paper under NH3. We found that nitrogen doping (up to 10.3 at %) occurs during cellulose pyrolysis under NH3 at as low as 550 °C. At 700 °C or above, N-doped carbon further reacts with NH3, resulting in a large surface area (up to 1973.3 m(2)/g). We discovered that the doped nitrogen, in fact, plays an important role in the reaction, leading to carbon gasification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
209
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(225 citation statements)
references
References 53 publications
14
209
0
2
Order By: Relevance
“…The amount of doped N for the NCPE was ~ 7 wt%, based on the XPS results. The N1s spectrum for the NCPE contained two peaks at 397.7 and 400.4 eV, as shown in Figure 3c, which were in good agreement with the binding energies of the pyridinic and pyrrolic N [22,41], respectively. Therefore, it is evident that nitrogen atoms were doped into the carbon lattice instead of dangling on the carbon surface.…”
Section: Characterizationsupporting
confidence: 68%
“…The amount of doped N for the NCPE was ~ 7 wt%, based on the XPS results. The N1s spectrum for the NCPE contained two peaks at 397.7 and 400.4 eV, as shown in Figure 3c, which were in good agreement with the binding energies of the pyridinic and pyrrolic N [22,41], respectively. Therefore, it is evident that nitrogen atoms were doped into the carbon lattice instead of dangling on the carbon surface.…”
Section: Characterizationsupporting
confidence: 68%
“…The creation of carbon vacancies may be attributed to the reaction between some carbon species of GCN with ammonia at high temperature. [ 23 ] Considering many different types of carbon species in GCN, further mechanistic study is undergoing to verify this assumption. The C 1s and N 1s spectra are almost the same for both BGCN and HGCN (Figure 4 F), further indicating that NH 3 etching has little infl uence on the CN aromatic systems.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, transmission electron microscopy (TEM) images (Figure 3 d-g) disclosed the presence of micropores in the NPCs, which were possibly generated during PI decomposition and the activation process. [30][31][32] Moreover, high-resolution TEM (HRTEM) images of NPCs showed that the highly crystalized carbon frameworks of NPCs had an interplanar spacing of ≈0.34 nm ( Figure S9, Supporting Information), which corresponded with the (002) facet of graphitic carbon. Consistent with the HRTEM results, the XRD profi les of the NPCs also revealed two peaks at ≈26° and 44° indexed to the (002) and (101) planes of graphite, respectively, confi rming the formation of a graphitic framework in the NPCs ( Figure S10, Supporting Information).…”
Section: Doi: 101002/adma201505131mentioning
confidence: 99%